Customer Perception Towards Credit Management System of Public Sector Banks in Puducherry Region - M. Madhuranjani; Baig Mansur Ibrahim, (Journal of Accounting Research, Business and Finance Management (e-ISSN: 2582-8851), 2024)
This research project explores the customer perception towards the credit management system of public sector banks in the Puducherry region. Focusing on public sector banks in Puducherry, the study aims to evaluate customer perceptions, identify strengths and weaknesses in credit management practices, and provide recommendations for improvement. A comprehensive survey collected customer data regarding their experiences with credit approval processes, risk assessment, communication, and product utilization. Key recommendations include tailoring credit services to meet varying customer needs, enhancing transparency in communication, expediting the credit approval process, improving user-friendliness, and providing comprehensive education on credit products. By addressing these recommendations, public sector banks in Puducherry can strengthen their position in the banking industry and better align their practices with evolving customer expectations, fostering a more customer-centric approach to credit management. This research contributes valuable insights to the discourse on effective credit management practices, specifically within the context of public sector banks in the Puducherry region.